Pengaruh Perputaran Kas, Perputaran Piutang, Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Konstruksi yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Riky Guspian Fauzi; I Nengah Arsana; Lalu Mimbar (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the effect of Cash Turnover, Receivables Turnover, Inventory Turnover on Profitabillity partially, to determine the effect of Cash Turnover, Receivables Turnover, Inventory Turnover on Profitability simultaneously, and to determine the most dominant variable affecting Profitability in Construction Companies. The approach in this study is to use an associative approach. The population in this study were all construction companies listed on the Indonesia Stock Exchange in 2018-2022, namely 26 companies and the research sample was 8 companies. The data analysis technique used is multiple linear regression analysis, classical assumption test, t test, f test and determination coefficient, and beta coefficient. The results of this study indicate that, partially, cash turnover and inventory turnover have no significant effect on profitability, while accounts receivable turnover has a significant effect on profitability. simultaneously Cash turnover, accounts receivable turnover, inventory turnover have a significant effect on profitability. And the most dominant variable receivable turnover affects profitability